2013
DOI: 10.1371/journal.pone.0082559
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the piggyBac Transposon Using mRNA and Insulators: Toward a More Reliable Gene Delivery System

Abstract: Integrating and expressing stably a transgene into the cellular genome remain major challenges for gene-based therapies and for bioproduction purposes. While transposon vectors mediate efficient transgene integration, expression may be limited by epigenetic silencing, and persistent transposase expression may mediate multiple transposition cycles. Here, we evaluated the delivery of the piggyBac transposase messenger RNA combined with genetically insulated transposons to isolate the transgene from neighboring r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 40 publications
1
27
0
Order By: Relevance
“…The low rate of conventional rAAV integration was strategically exploited to minimize persistent piggyBac transposase expression, which could cause multiple transposition cycles, leading to eventual loss of transposons and therefore therapeutic transgene expression, and additionally could increase damage to the genome through aberrant chromosomal break repair and recombination events . Thus, to add to the biosafety and efficacy of this hybrid vector system, a further advancement would be to deliver a more labile source of transposase expression, such as mRNA using lipid nanoparticles.…”
Section: Discussionmentioning
confidence: 99%
“…The low rate of conventional rAAV integration was strategically exploited to minimize persistent piggyBac transposase expression, which could cause multiple transposition cycles, leading to eventual loss of transposons and therefore therapeutic transgene expression, and additionally could increase damage to the genome through aberrant chromosomal break repair and recombination events . Thus, to add to the biosafety and efficacy of this hybrid vector system, a further advancement would be to deliver a more labile source of transposase expression, such as mRNA using lipid nanoparticles.…”
Section: Discussionmentioning
confidence: 99%
“…However, we have some problems to be solved in this study: (i) we need to generate CAR T cells from leukemic patients treated with cytotoxic agents and/ or TKIs who are probably poor responders, (ii) we have no comparative data on the anti-leukemic potency of CAR T cells between retro/lentiviral and piggyBac gene modifications, (iii) we used an anti-CH2CH3 antibody, which is not compliant to cGMP, for selection of CAR-expressing T cells and culture plates inappropriate to cGMP, and (iv) we observed relatively high copy number integration of CD19.CAR-transposon plasmids (~5 copies per cell) with residual piggyBac -transposase plasmids (~2 copies per cell), which may be a potential risk of unexpected T-cell transformation, re-transposition of a transgene, or rejection of infused T cells in patients if expressing piggyBac protein. Regarding the safety concerns, co-delivery of a suicide gene or use of piggyBac -transposase mRNA may be helpful (11,13,31). All things considered, clinical-grade DNA plasmids are inexpensive and easy to manufacture relative to viral vectors; therefore, the piggyBac -transposon system in combination with our T-cell culture system would increase the cost-benefit and safety of CAR-modified T-cell therapy, thereby facilitating regulatory approval.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, employment of a more labile (therefore, showing a short half-life) source of transposase, such as PB transposase mRNA or protein, is desirable. Indeed, efficient transposition using in vitro-transcribed PB transposase mRNAs has been documented in various species including mammals [89][90][91]. Notably, PB transposase mRNA (Improved Super piggyBac transposase mRNA) is now commercially available from Transposagen Biopharmaceuticals, Inc. (#SPB-100; Lexington, KY, USA).…”
Section: Pb Transposase Mrnamentioning
confidence: 99%
“…Expression of a GOI is guaranteed when it is placed between two insulators, which prevents propagation of a silencing chromatin structure over the GOI. Bire et al [89] demonstrated the effectiveness of insulators for increasing the expression rate of a GOI after PB-based gene delivery.…”
Section: Use Of Insulatorsmentioning
confidence: 99%